2014
DOI: 10.1088/0029-5515/54/10/103007
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of H and He, and their effects on vacancy evolution in tungsten in a fusion environment

Abstract: The behaviours of hydrogen and helium in tungsten are vitally important in fusion research because they can result in the degradation of the material. In the present work, we carry out density-functional theory calculations to investigate the clustering of hydrogen and helium atoms at interstitial sites, vacancy and small vacancy clusters (Vac m , m = 2, 3), and the influence of hydrogen and helium on vacancy evolution in tungsten. We find that hydrogen atoms are extremely difficult to aggregate at interstitia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
68
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 62 publications
17
68
1
Order By: Relevance
“…It is well known that in tungsten an interstitial hydrogen atom prefers to occupy the tetrahedral interstitial site (TIS) rather than the octahedral interstitial site (OIS), and the interstitial H-H interaction is generally repulsive. [7][8][9][10][11] These have also been confirmed by our current calculations where the TIS is found to be 0.38 eV more stable than the OIS for a hydrogen atom. Our preliminary calculations also show that all TIS-OIS hydrogen pairs, OIS-OIS hydrogen pairs, and OIS hydrogen self-clusters are energetically unfavorable or unstable compared with the pure TIS ones.…”
Section: Configurations and Binding Energetics Of Stable H N Self-clusupporting
confidence: 85%
See 1 more Smart Citation
“…It is well known that in tungsten an interstitial hydrogen atom prefers to occupy the tetrahedral interstitial site (TIS) rather than the octahedral interstitial site (OIS), and the interstitial H-H interaction is generally repulsive. [7][8][9][10][11] These have also been confirmed by our current calculations where the TIS is found to be 0.38 eV more stable than the OIS for a hydrogen atom. Our preliminary calculations also show that all TIS-OIS hydrogen pairs, OIS-OIS hydrogen pairs, and OIS hydrogen self-clusters are energetically unfavorable or unstable compared with the pure TIS ones.…”
Section: Configurations and Binding Energetics Of Stable H N Self-clusupporting
confidence: 85%
“…Based on Eqs. (9)(10)(11)(12), the Gibbs free energy change of the system as a function of the self-cluster size n at different C H and T = 300 K is plotted in Figure 6a. We see that the enthalpy term ∆H decreases monotonically as n increases, with the rate of change in ∆H first accelerating and then gradually stabilized at a constant rate.…”
Section: Thermodynamic and Kinetic Analyses Of H Self-clusteringmentioning
confidence: 99%
“…In our previous study, it was found that He atoms preferred to diffuse and cluster along one certain crystal face at an elevated temperature, leading to surface swelling of He-enriched strips [12]. Helium atoms are energetically favorable to cluster together in a close-packed arrangement between (110) planes forming helium monolayer structure [20]. Charlotte S. Becquart and Christophe Domain have proved that He atoms can be trapped by other He atoms and can explain the formation of He blisters close to the surface of He implanted tungsten [21].…”
Section: Discussionmentioning
confidence: 99%
“…High heat fl uxes are expected in the divertor, apart from neutron, He, H atoms, and ions bombardments. Theory [31] indicates that He and H coimplantation in W can cause similar blistering as in Si. However, tests simulating the fusion environment indicated that exposure of W to deuterium atmosphere but seeded with He could result in suppression of blisters, see, for example, [32,33].…”
Section: Case Study III -Materials For Fusion Reactorsmentioning
confidence: 99%
“…Factors for this opportunity are: -subjects that found a methodological barrier when using traditional investigations [23], -new challenges for material in manufacturing consumables, transportation, energetics, environmental protection, and healthy societies, -global, expanding outside EU search for positron answers [31], -growing scientifi c infrastructures in 'emerging' countries, -vast EU experience in projecting positron beams [8, 14-18, 40, 46, 48, 49]. …”
Section: Toward a European Networkmentioning
confidence: 99%